Central bank digital currency - Aleksi Grym; Päivi Heikkinen; Karlo Kauko; Kari Takala (Bank of Finland, 2017)
Central banks have traditionally issued cash to the general public. With digitalisation, banknotes are becoming a technically outdated payment instrument, and some central banks have explored the possibility of central bank-issued electronic money applicable to retail payments. Electronic central bank money would offer the public the possibility to hold central bank money in a potentially cashless future. In its present form, blockchain technology would probably not be a suitable solution, since it is unable to process a sufficiently large number of transactions. Electronic central bank money would potentially have significant implications for other areas of central bank policy, which should be meticulously analysed.
URN:NBN:fi:bof-201711211668; Additional information: This article was originally published in Finnish under the title ”Digitaalinen keskuspankkiraha”, BoF Economics Review 4/2017: http://urn.fi/URN:NBN:fi:bof-201711031665
Keywords: G21; E58; E42; 330; money; central banks